Stable Ag2O/g-C3N4 p-n heterojunction photocatalysts for efficient inactivation of harmful algae under visible light - Fan, Gongduan; Du, Banghao; Zhou, Jinjin; Yu, Weiwei; Chen, Zhuoyi; Yang, Shangwu (Applied catalysis. B, Environmental, 2020)
[Display omitted] •Bulk g-C3N4 with negative charge surface tended to form the p-n heterojunction.•Photocatalytic activity of the heterojunction was affected by composition ratio.•Photocatalytic activity 14.3 wt% Ag2O/B-g-C3N4 was good for algae inactivation.•Predominant O2− damaged the antioxidant system of algae cells and released ions. The design of stable and highly efficient photocatalysts for harmful algae removal is critical to preserve the aquatic ecosystems. In this work, a series of Ag2O/g-C3N4 with p-n heterojunction were synthesized by a chemical deposition method for photocatalytic algae removal under visible light. The effects of surface charge and composition ratio for the formation of heterojunction were investigated. The crystal phase, functional groups, morphology, optical properties, and elemental composition of the synthesized photocatalysts were also characterized. The experimental results showed that the photocatalytic activity of 14.3 wt% Ag2O/B-g-C3N4 was outstanding for algae removal, suggesting that the bulk graphitic carbon nitride (g-C3N4) with negative surface charge was subject to combine with Ag2O to form the heterojunction. In addition, the photocatalytic activity of the heterojunction was greatly affected by the composition ratio of synthesized materials. The optimal photocatalytic activity was observed when the composition ratio of Ag2O and bulk g-C3N4 was 1:6, and the photocatalyst reached up to 99.94 % removal of Microcystis aeruginosa (M. aeruginosa) after 6 h of photocatalytic reaction. Superoxide dismutase (SOD) and malondialdehyde (MDA) of algae cells decreased while catalase (CAT) increased during the experimental process. Furthermore, the antioxidant system collapsed and algal cell membrane was ruptured and damaged, resulting in the release of a large number of important ions (e.g., K+, Ca2+, and Mg2+), the decrease of chlorophyll a and phycobiliprotein (PB) contents, as well as the destruction of the photosynthetic system. Overall, the synthesized 14.3 wt% Ag2O/B-g-C3N4 as a good photocatalyst has remarkable photostability under visible light and can be applied to alleviate cyanobacteria blooms.